A Deixis Analysis in The Short Story “A Ghost” by Guy de Maupassant - Nur Azizah Fitriani, Dwi (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2023)
The study aims to analyze the deixis in "A Ghost" short stories written by Lewis Caroll. "A Ghost" is a fictional horror about a horror case happen to the old Marquis de la Tour-Samuel when he was young. Deixis refers to the way speakers orient themselves and their listeners in terms of discourse, person, times, space and social in relation to the immediate situation of speaking. The method used in this research is a descriptive qualitative method that includes the stages of data collection, analyzing the data and then making a conclusion about it. Deixis helps the readers to easily understand about the content of the story.